MORPHOLOGICAL FEATURES OF REGENERATION OF THE ACHILLES TENDON AFTER ITS CROSS TENOTOMY WITH INTERSECTION OF FASCIAL SHEATHS AND DAMAGE OF MESENTERIC VESSELS - M. V. Vlasov; S. N. Bugrov; A. B. Bogos’Yan; I. V. Musikhina (Вестник хирургии имени И.И. Грекова, 2016)
The article is aimed to study morphological features of regeneration process of the Achilles tendon after its cross tenotomy with intersection of facial sheaths and damage of mesenteric vessels in experiment on growing rabbits. The experiment was made on 25 rabbits of «Shinshilla» breed of both sexes in the age of one month with the mass of 1376±124,8 g. The processes of reparative regeneration of heel tendon were investigated. There was used a rabbit’s output from the experiment on 15, 21,30,60 and 90 days after cross tenotomy in number of five animal units. According to results of carried out researches, the considerable part of defect was completed by dense connective tissue obtaining scarry character on 60 days. There was observed an opposite development of defect zone, a focal substitution of dense fibrous tissue by loose connective tissue with histiocytic, lymphoid cells and inclusions of foci of fatty tissue on 90 days. The authors didn’t noted the complete recovery of tendinous tissues «retitucica ad integrum» in the zone of tenotomy, because of circulatory disturbance in this area due to damage of facial sheats and mesenteric vessels. Thereby, the reparative regeneration of heel tendon was originated in unfavorable conditions, because of cross tenotomy performance with intersection of synovial sheath and damage of mesenteric vessels. The results obtained indicated that it is necessary to avoid the damage of synovial sheathes and mesenteric vessels in cross intersection of heel tendon during correction of foot element deformations.